Experimental Study on the Effect of Magnetic Fields on Combustion Characteristics of Biodiesel from Nyamplung (Calophyllum Inophyllum) - Imam Rudi Sugara; Nasrul Ilminnafik; Salahuddin Junus; Muh Nurkoyim Kustanto; Yuni Hermawan (Universitas Muhammadiyah Magelang, 2023)
Nyamplung (Calophyllum Inophyllum) is an environmentally friendly alternative fuel that can be used to replace the consumption of fossil fuels. The purpose of this experiment was to analyze the effect of magnetic fields on the premixed flame of biodiesel from Calophyllum Inophyllum, the experiments were carried out on a bunsen burner. Fuel evaporation uses a temperature of 473 K and the equivalent ratio used is between Ï• 0.7; 0.8; 0.9; 1.0; 1.1 and 1.2. This experiment used a modified magnet that has magnetic force in 11.000 gausses with magnetic variations N-S, S-N, N-N, and S-S. Experiments revealed that magnetic fields have a significant effect to increase the value of laminar flame speed on magnetic variations point at S-S 3.8%; N-N 4.8%; S-N 17.09%, and the highest laminar flame speed were at point N-S 20.7%. The enhancement value of laminar flame speed indicated more optimum combustion processes. The magnetic fields can influence the O2, and H2O and change the orientation of the hydrocarbons which makes it easier for O2 and fuel to carry out the oxidation process, resulting in more optimal combustion.